Impact of Interest and Motivation on Academic Achievement of Junior Secondary School Students in Mathematics - Asanre, Akorede; Sondlo, Aviwe; Abiodun, Taiwo (Journal of Mathematics Instruction, Social Research and Opinion, 2024)
This research study investigated the influence of interest and motivation on mathematics achievement among junior secondary school students in Ijebu Ode, Ogun State, Nigeria. The study methodology was a descriptive survey, and the sample size of 350 junior secondary school students in Ijebu Ode from five public schools was chosen using a simple random sampling procedure. The Mathematics Achievement Test (MAT) and the Interest and Motivation towards Learning Mathematics Scale (IMLMS), with reliability coefficients of 0.77 and 0.81, respectively, were used in the study. Multiple regression analysis, Pearson Product Moment Correlation, and descriptive statistics were used to analyze the data gathered. The results showed that motivation and interest positively impact student achievement in school. They further demonstrated the independent factors' combined influence on the dependent variables. Based on the results, it is determined that junior secondary school students in Ijebu Ode, Ogun State, Nigeria, have high academic achievements in mathematics and that both motivation and interest jointly predict academic achievement. To improve students' mathematics achievement, it is advised that schools actively support these factors during the teaching and learning processes. The Ministry of Education needs to require all schools to implement student-motivating policies.